2021
DOI: 10.1002/bit.27807
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of protein production by engineering a novel antiapoptotic baculovirus vector to suppress the expression ofSf‐caspase‐1andTn‐caspase‐1

Abstract: The baculovirus expression vector system (BEVS) is an attractive manufacturing platform for recombinant protein production in insect cells. However, baculovirus infection commonly induces host apoptosis in 3-4 days which would subsequently terminate the protein expression. Previous studies have proved that protein production by BEVS can be elevated in apoptosis-suppressed insect cells. We also developed a baculovirus vector in our previous report to inhibit the apoptosis and improve protein production in Sf9 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The inhibition of pre-apoptotic (e.g., dronc) [62] and apoptotic (e.g., caspase-1) gene expression has already been shown, indicating slight improvements. [63][64][65][66][67] However, a recent study repressing Caspase-1 activity does not correlate to these findings, indicating no significant increase in productivity and prolonged cell survival, [68] as Caspase-1 activity may already be inhibited by viral anti-apoptotic genes such as the viral P35 protein. [69] Nevertheless, other differential expressed apoptotic-related genes observed in this study may proof functionality in delaying apoptosis and/or improving productivity in IC-BEVS.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of pre-apoptotic (e.g., dronc) [62] and apoptotic (e.g., caspase-1) gene expression has already been shown, indicating slight improvements. [63][64][65][66][67] However, a recent study repressing Caspase-1 activity does not correlate to these findings, indicating no significant increase in productivity and prolonged cell survival, [68] as Caspase-1 activity may already be inhibited by viral anti-apoptotic genes such as the viral P35 protein. [69] Nevertheless, other differential expressed apoptotic-related genes observed in this study may proof functionality in delaying apoptosis and/or improving productivity in IC-BEVS.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of this study, we were unable replicate previously reported results that the RNAi‐mediated suppression of Caspase‐1 in lepidopteran cells can improve BEVS yields. [ 15–17,41 ] There are several possible explanations to account for this result. Firstly, previous studies exploring RNAi knockdown of Caspase‐1 in lepidopteran cells almost exclusively utilized static culture and media containing fetal bovine serum to undertake BEVS infection experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have documented that RNAi-based silencing of Sf-Caspase1 in Sf9 cells could improve the recombinant protein production of the BEVS. [15,[39][40][41] It is possible that reducing Sf-Caspase-1 expression, rather than eliminating it completely, could account for the discrepancy between the effects of RNAi knockdowns and CRISPR-Cas9 knockouts on recombinant protein production. To explore this possibility, Sf9 cell lines stably expressing RNAi constructs targeting Sf-Caspase-1 were generated via transfection with plasmids designed to reproduce two previously published constructs.…”
Section: Establishment Of Rnai-expressing Sf9 Cell Lines Stably Suppr...mentioning
confidence: 99%
“…(B) Schematic diagram of Bac563-5 T used in this study. Bac563-5 T was modified from BAC10:KO1629 by knocking out ChiA/v-cath (Ac126-127) and p10 (Ac137) and inserting an shRNA expression cassette at the Ac137 locus to inhibit the virus infection-induced apoptosis (Je et al, 2001a;Zhang et al, 2021Zhang et al, ). 10.3389/fmicb.2023 Frontiers in Microbiology 05 frontiersin.org genome for better expression of foreign genes and insertion of larger exogenous DNA fragments, we generated 14 fragment-knockout (KO) bacmids based on BAC10:KO1629 (Table 2).…”
Section: Construction Of Acmnpv Fragment-knockout Bacmidsmentioning
confidence: 99%